Análisis para el diseño de un sistema que gestione la bolsa de empleo y pasantías en la FAFI usando metodología XP Programming. - Cabezas Orellana, Hugo Eliezer (2023)
This case study addresses the analysis for the design of a system to manage the employment and internship exchange at the Faculty of Administration, Finance and Informatics (FAFI) of the Technical University of Babahoyo, using the XP Programming methodology. The main objective is to provide students and graduates with access to job opportunities and companies with the possibility of selecting the most suitable candidates for their needs. Interviews with the coordinator of the faculty's employment exchange and surveys of graduates were carried out to identify the main requirements and needs of students and graduates, which allowed defining the essential functionalities and features of the proposed system. In addition, a database structure was designed, the main modules of the system were defined and the user interfaces were designed. The technical, economic and operational feasibility of the project was analyzed, concluding that it is viable and that its implementation could generate significant benefits for FAFI, its students and graduates, as well as for companies interested in hiring professionals trained at this institution. This case study has made it possible to develop a detailed analysis for an internship and employment exchange management system at FAFI, taking into account the needs and expectations of the actors involved and using a methodology appropriate to the project. The implementation of this system could generate significant benefits for FAFI, its students and graduates, and companies interested in hiring professionals trained at this institution.